KAP:location privacy-preserving approach in location services - Yu-hang WANG; Hong-li ZHANG; Xiang-zhan YU (Tongxin xuebao)
Preserving location privacy is an essential requirement in mobile internet.A location privacy protection approach named KAP was proposed which aimed at the privacy issue of location service under the mobile Internet.Through the analysis on locating technology，a weighted adjacent graph-based topology model was given in order to describe the positional relationship between hot spots.Meanwhile，with the help of the model，combining the concept of k-anonymity，three privacy algorithms was shown to make sure the location can not be obtained precisely by attacker.The simulation results verified the correctness and performance of the approach.